2013
DOI: 10.1128/jb.02269-12
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Escherichia coli SecA Dimer Interface Residues through In Vivo Site-Specific Photo-Cross-Linking

Abstract: The motor protein SecA is a core component of the bacterial general secretory (Sec) pathway and is essential for cell viability. Despite evidence showing that SecA exists in a dynamic monomer-dimer equilibrium favoring the dimeric form in solution and in the cytoplasm, there is considerable debate as to the quaternary structural organization of the SecA dimer. Here, a site-directed photo-cross-linking technique was utilized to identify residues on the Escherichia coli SecA (ecSecA) dimer interface in the cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
(77 reference statements)
3
27
0
Order By: Relevance
“…6). A separate, extensive in vivo photocrosslinking study identified crosslinks that were not consistent with any one dimer (171). This may mean that in vivo minor populations of several dimeric forms exist and were trapped.…”
Section: Seca An Atpasementioning
confidence: 99%
“…6). A separate, extensive in vivo photocrosslinking study identified crosslinks that were not consistent with any one dimer (171). This may mean that in vivo minor populations of several dimeric forms exist and were trapped.…”
Section: Seca An Atpasementioning
confidence: 99%
“…To address this, we employed an alternate method to confirm which of the eIF3c, -d, -l, and -e subunits interact with eIF4G. The unnatural amino acid p-benzoylphenylalanine (Bpa) has been used recently to explore multi-factor interactions in vivo and in vitro in bacteria, yeast, and mammalian systems (31)(32)(33)(34)(35)(36). Bpa is photoactivatable at 350 -360 nm, preferentially reacts with C-H bonds versus water, and can be activated reversibly.…”
Section: Human Eif4gmentioning
confidence: 99%
“…The low efficiency of this technique in comparison to disulfide crosslinking assures that it is minimally perturbing of any natural protein interaction equilibrium. This approach has been utilized previously to map both the SecA-SecY and SecA dimer interfaces (Mori and Ito 2006, Das and Oliver 2011, Yu, Wowor et al 2013), although only cytosolic SecA was examined in the latter study with somewhat equivocal results.…”
Section: Introductionmentioning
confidence: 99%